Natural Killer Cell Diversity in Viral Infection: Why and How Much? - Catherine A. Blish (Case Western Reserve University, 2016)
Natural killer cells are a diverse group of innate lymphocytes that are specialized to rapidly respond to cancerous or virus-infected cells. NK cell function is controlled by the integration of signals from activating and inhibitory receptors expressed at the cell surface. Variegated expression patterns of these activating and inhibitory receptors at the single cell level leads to a highly diverse NK cell repertoire. Here I review the factors that influence NK cell repertoire diversity and its functional consequences for our ability to fight viruses.